2020
DOI: 10.1055/s-0040-1715097
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes, Health Care Costs and Prognostic Factors for Total Knee Arthroplasty: A Multilevel Analysis of a National Cohort Study Using Administrative Claims Data

Abstract: Total knee arthroplasty (TKA) is one of the most frequent orthopaedic surgeries. The purpose of this study was to determine the 30-day postoperative mortality rate, total episode-of-care costs, and prognostic factors associated with these outcomes, for adult patients who underwent TKA in Colombia's contributory health care system. A retrospective cohort study of all adult patients enrolled in Colombia's contributory health system, who underwent TKA between January 1, 2012 and November 30, 2015 was performed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
2
5
0
1
Order By: Relevance
“…The literature on the relationship between CCI score and post-TKA mortality is sparse yet consistent in finding a significant association between high CCI score with increased mortality risk. 4 40 Buitrago et al 4 conducted a study of 12,453 TKA patients and found that those with a CCI score ≥ 3 had a 30-day mortality odds ratio of 7.59 (95% CI: 1.79–32.10, p = 0.01). Of note, this study included all TKA procedures inclusive of revision and emergent procedures and was conducted with a Colombian patient population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on the relationship between CCI score and post-TKA mortality is sparse yet consistent in finding a significant association between high CCI score with increased mortality risk. 4 40 Buitrago et al 4 conducted a study of 12,453 TKA patients and found that those with a CCI score ≥ 3 had a 30-day mortality odds ratio of 7.59 (95% CI: 1.79–32.10, p = 0.01). Of note, this study included all TKA procedures inclusive of revision and emergent procedures and was conducted with a Colombian patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Total knee arthroplasty (TKA) is a widely utilized procedure with excellent functional outcomes and long-term survivorship. 1 2 3 4 5 Although mortality after TKA is rare, it remains an ever-present concern given its catastrophic nature and potential for aversion through nonoperative management. Thirty-day mortality rates between 0.17 6 and 0.5% 7 following primary elective TKA have been reported in the literature.…”
mentioning
confidence: 99%
“…En este análisis inicial relacionamos la tasa de mortalidad perioperatoria en el departamento de Tolima. Este abordaje permite obtener datos más actualizados y representativos en nuestro territorio, en contraste con la evidencia que ofrecen los estudios retrospectivos 5,[18][19][20][21] .…”
Section: Fortalezas Y Limitacionesunclassified
“…This database contains detailed information about all health services that are used by the individuals in the contributory system, and includes the identi cation of the type of service provided, the associated ICD-10 code, the cost paid by the insurer, the date of service, the municipality and the provider. This database is highly standardized, has little underreporting of the health services provided to the enrolled population and has already been used in other national studies (25)(26)(27)(28)(29)(30)(31)(32). 2) Another source of information that was used was the Unique Enrollee Database (BDUA in Spanish), which contains information about all enrollees in the health system, including enrollment status, age, sex, insurer and the health system in which the person was enrolled.…”
Section: Sources Of Informationmentioning
confidence: 99%